AUTOMATIC DRYER FOR DRYING RHIZOMES IN THE PUSPASARI WOMEN FARMERS GROUP - Al Kindi, Hablinur; Siregar, Tika Hafzara; Sutisna, Setya Permana; Sutoyo, Edi; Akbar, Barkah; Nashrullah, Nuruddin (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
One form of community service is the transfer of technology from universities to community groups. The Puspasari Women's Farmers Group (KWT) has a medicinal plant garden that produces medicinal plants, one of which is rhizomes. One of the shortcomings of drying the rhizomes is the drying process which is still conventional, this causes the quality of the rhizomes to be poor. The purpose of this service is, with the presence of an automatic dryer owned by the agricultural engineering study program of Ibn Khaldun University, it is hoped that there will be an increase in product quality and an increase in the understanding of KWT members regarding drying. After the implementation of the dryer training, training participants were given questionnaires and questions. As a result, the participants stated that the drying results with the automatic drying tool were much better than conventional drying. Participants were able to answer 60% of the questions given regarding basic drying knowledge.